KS02.4.A Olaparib in Recurrent IDH-mutant High-Grade Glioma (OLAGLI). (9th September 2021) - Ducray, F; Sanson, M; Chinot, O; Fontanilles, M; Rivoirard, R; Thomas-Maisonneuve, L; Cartalat, S; Tabouret, E; Bonneville-Levard, A; Darlix, A; Ameli, R; Meyronet, D; et al.
Abstract: BACKGROUND: There is a need to develop new treatments in IDH-mutant high-grade gliomas recurring after radiotherapy and chemotherapy. Based on preclinical studies showing that IDH-mutant tumors could be vulnerable to PARP inhibition we launched a phase II study to test the efficacy of olaparib (Lynparza) monotherapy in this population. METHODS: Adults with recurrent high-grade IDH-mutant gliomas after radiotherapy and at least one line of alkylating chemotherapy (PCV or TMZ), KPS > 60, normal organ function were enrolled. The primary endpoint was 6 months PFS according to RANO criteria. Patients were treated with olaparib 300 mg twice daily. We used a single-stage Fleming design with p0 = 30%, p1 = 50%, a type I unilateral error rate of 5% and a power of 80%. RESULTS: 35 patients with recurrent IDH-mutant gliomas (IDH1R132H-mutant n = 32, other IDH mutation n = 3, 1p/19 codeleted n = 16, 1p/19q non-codeleted n = 14) were enrolled (malignantly transformed low-grade gliomas n = 21, anaplastic gliomas n = 8, glioblastomas n = 6). Median time since diagnosis was 7.4 years (1–22 years), median time since radiotherapy was 2.8 years (0.6–18 years), median number of previous chemotherapy lines was 2 (1–5). With a median follow-up of 11 months, 30 patients had stopped treatment due to tumor progression and 2 patients were still on treatment 16 to 18 months after treatment start. At 6 months, 11/35 patients were progression-free (31 %). According to RANO criteria, based on local investigator analysis, 2 patients (5%) had a partial response and 14 patients a stable disease (37%) with a median duration of response of 9 months (4–18+). Median PFS and OS were 2.3 and 15.9 months and were similar in 1p/19q codeleted and non-codeleted patients. A grade 3 olaparib-related adverse event was observed in 5 patients (14%, lymphopenia n = 3, fatigue n = 2, diarrhea n = 1) and a grade 2 in 15 patients (43%), most frequently consisting in fatigue (23%), gastrointestinal disorders (20%) and lymphopenia (20%). No patient definitively stopped olaparib due to side effects. CONCLUSIONS: In this heavily pre-treated population of recurrent IDH-mutant gliomas, olaparib monotherapy was well tolerated and resulted in some activity supporting its evaluation in association with alkylating chemotherapy in recurrent IDH-mutant gliomas in future studies.